2020
DOI: 10.1101/2020.04.25.061440
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide association analysis reveals new insights into the genetic architecture of defensive, agro-morphological and quality-related traits in cassava

Abstract: Cassava (Manihot esculenta) is one of the most important starchy root crops in the tropics due to its adaptation to marginal environments. Genetic progress in this clonally propagated crop can be accelerated through the discovery of markers and candidate genes that could be used in cassava breeding programs. We carried out a genome-wide association study (GWAS) using a panel of 5,310 clones developed at the International Institute of Tropical Agriculture - Nigeria. The population was genotyped at more than 100… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 76 publications
2
24
0
Order By: Relevance
“…Interestingly, we found that traits with the most accurately predicted variances had less accurately predicted means, including the SIs (mean: StdSI < BiofortSI; variance: StdSI > BiofortSI; Figures 1 and 2 ). This does not seem initially explainable by our priors regarding trait genetic architectures; DM and FYLD are both generally considered as polygenic/infinitesimal traits, while MCMDS and TCHART are expected to be closer to mono- or oligogenic ( Wolfe et al 2016b ; Rabbi et al 2020 ). Differences in accuracy between mean and variance predictions should instead have to do with the nature of linkage disequilibrium, especially as it affects marker-causal relationships ( de Los Campos et al 2015 ; Lehermeier et al 2017a ).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Interestingly, we found that traits with the most accurately predicted variances had less accurately predicted means, including the SIs (mean: StdSI < BiofortSI; variance: StdSI > BiofortSI; Figures 1 and 2 ). This does not seem initially explainable by our priors regarding trait genetic architectures; DM and FYLD are both generally considered as polygenic/infinitesimal traits, while MCMDS and TCHART are expected to be closer to mono- or oligogenic ( Wolfe et al 2016b ; Rabbi et al 2020 ). Differences in accuracy between mean and variance predictions should instead have to do with the nature of linkage disequilibrium, especially as it affects marker-causal relationships ( de Los Campos et al 2015 ; Lehermeier et al 2017a ).…”
Section: Discussionmentioning
confidence: 85%
“…The pedigree and germplasm chosen represent parents and offspring from the first three cycles of GS conducted at the International Institute of Tropical Agriculture (IITA). These germplasm and genomic selections have been described in greater detail previously ( Rabbi et al 2017 , 2020 ; Wolfe et al 2016a , b , 2017 , 2019 ). We note that each cycle of selection was done by recurrent genomic truncation selection using a SI similar (but not identical) to the one described below.…”
Section: Methodsmentioning
confidence: 99%
“…The advantage of GWAS over QTL mapping is the higher mapping resolution and the identification of a broader set of alleles in large diverse germplasm (Yu and Buckler, 2006). Several GWAS have been conducted on key cassava traits, including CMD resistance (Rabbi et al, 2020; Wolfe et al, 2016), carotenoids content (Esuma et al, 2016; Ikeogu et al, 2019; Rabbi et al, 2017, 2020) and dry matter content (Rabbi et al, 2020) in diverse cassava populations to discover significant loci.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding genetic diversity of species is the basis for a breeding program and to develop strategies for germplasm collection, management, conservation and improvement for food security and sustainable agricultural development [9, 10, 11]. Genetic diversity studies have widely been done for cassava using both morphological and molecular methods in other countries such as Brazil [12], Chad [13], Benin Republic [14], Nigeria [15] etc. but not Burundi.…”
Section: Introductionmentioning
confidence: 99%
“…The utilization of SNPs has gained popularity in recent years due to their abundance, ubiquitous nature, polymorphism and amenability to automation [25]. In cassava, SNPs have been used for genetic linkage mapping [26, 27], genome-wide association studies [15] and genetic diversity assessments [28]. Diversity Arrays Technology (DArT) markers for cassava were developed and reported as a tool for genotyping large germplasm collections [29] but this has not been used on Burundian cassava genotypes.…”
Section: Introductionmentioning
confidence: 99%